2019
DOI: 10.1111/ner.12910
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Electrical Charge Delivery on Inhibition of Mechanical Hypersensitivity in Nerve-Injured Rats by Sub-Sensory Threshold Spinal Cord Stimulation

Abstract: Objectives Spinal cord stimulation (SCS) represents an important neurostimulation therapy for pain. A new ultra‐high frequency (10,000 Hz) SCS paradigm has shown improved pain relief without eliciting paresthesia. We aim to determine whether sub‐sensory threshold SCS of lower frequencies also can inhibit mechanical hypersensitivity in nerve‐injured rats and examine how electric charge delivery of stimulation may affect pain inhibition by different patterns of subthreshold SCS. Materials and Methods We used a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
(93 reference statements)
1
17
1
Order By: Relevance
“…Changes in mechanical hypersensitivity after SCS are also presented as PWTs in Supporting Information Figure S2. Overall, the inhibitory effects from both SCS paradigms in SCI rats were rather modest as compared to those we have reported for nerve-injured rats in our previous studies (24,25,29).…”
Section: Inhibitory Effects Of Scs On Mechanical Hypersensitivity In contrasting
confidence: 79%
See 2 more Smart Citations
“…Changes in mechanical hypersensitivity after SCS are also presented as PWTs in Supporting Information Figure S2. Overall, the inhibitory effects from both SCS paradigms in SCI rats were rather modest as compared to those we have reported for nerve-injured rats in our previous studies (24,25,29).…”
Section: Inhibitory Effects Of Scs On Mechanical Hypersensitivity In contrasting
confidence: 79%
“…Motor threshold (MoT) was determined by slowly increasing the amplitude of 4 Hz (0.2 msec) stimulation from zero until muscle contraction was observed in the mid‐lower trunk or hind limbs. Based on recent findings (20, 24, 25), we considered sensory threshold in awake rats to be near 50% MoT. Thus, conventional SCS (50 Hz, 0.2 msec) was conducted at 80% MoT (supra‐sensory threshold), and 1200 Hz, low‐intensity SCS (0.2 msec) was applied at 40% MoT (sub‐sensory threshold).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a follow-up report, Guan and coworkers [54] explored how charge delivery affects pain inhibition by different frequencies at intensities that seem to be below the sensory threshold (40% MT), and which component of stimulation runs the therapeutic actions. Epidural electrodes were implanted 5 to 7 days post-SNL, in a similar fashion described by this group previously [53].…”
Section: Heat Map Of Mean Module Eigengene Values For Modules With Simentioning
confidence: 99%
“…Numerous basic and clinical studies have now demonstrated that SCS can be therapeutically applied below the threshold of perception (i.e., sub-perception stimulation), in contrast to conventional methodologies traditionally utilized at or above perception threshold (i.e., supra-perception stimulation) [1,[11][12][13][14]. Although distinct mechanisms that underlie both of these SCS approaches have not been definitively identified, an assortment of reported studies and clinical observations seem to suggest that differences likely do exist with regard to how the analgesic outcomes induced by sub-and supra-perception SCS are manifested [15][16][17][18]. Given this probability and the dynamic nature of the chronic pain experience, there is now a growing interest in the clinical application of sub-and supra-perception SCS as a combination therapy versus the exclusive use of either subor supra-perception SCS alone [6,19,20].…”
Section: Introductionmentioning
confidence: 99%